Utilization of Terai Floodplain Grassland Communities by the Wild Mammals in Valmiki Tiger Reserve, Bihar, India - Murari, Krishna; Talukdar, Gautam; Jhala, Yadvenradev V.; Pandav, Bivash; Rawat, Gopal Singh (Indian Forester, 2025)
Endangered grassland-obligate fauna of the Terai region exhibit strong associations with distinct grassland communities across both managed and unmanaged grasslands. An understanding of grassland-mammal associations is essential for the management of the Terai floodplain grasslands. Valmiki Tiger Reserve (VTR) has the only relic of the Terai grassland remaining in Bihar. A total of 223 belt transects were laid on the already classified grassland communities for investigating the use of grassland communities by mammals. The Pellet groups and dung were counted in these belt transects. Ivlev’s Electivity Indices were computed to identify the preference of grassland vegetation community by mammals. Grasslands associations were established for chital, hog deer, nilgai, wild pig, domestic cattle and rufous tailed hare. Chital, hog deer, and domestic cattle preferred communities of S. munja as well as Imperata-Vetiveria- Typha-S. spontaneum, indicating high niche overlap and competition. Nilgai, wild pig, and rufous-tailed hare were found to prefer degraded association of Sclerostachya fusca, the tall wet association of Typha-S. arundinaceum and dry upland association of S. munja respectively. Since grassland management in Terai is necessary for augmenting the prey population, the Protected Area Managers should consider the preference of fauna for grassland communities, while practicing the management interventions such as cutting and burning.